An extraordinary new genus and three new species of Acostemmini (Hemiptera: Cicadellidae: Deltocephalinae) from Madagascar with comments on the morphology and classification of the tribe - Zahniser, J. N.; Nielson, M. W. (Zootaxa, 2012)
The circumscription and morphological characterization of the deltocephaline tribe Acostemmini is revised based on dis-coveries of new and poorly known taxa from recent collections in Madagascar and from examination of the type speci-mens of Alocoelidia fulva Evans, Iturnoria insulana Evans, and Protonesis delegorguei Spinola. Alocoelidia Evans 1954,Caelidioides Signoret 1880, Iturnoria Evans 1954, and Protonesis Spinola 1850 were previously placed in Coelidiinaebut were later removed from the subfamily and until now have been unplaced to subfamily are placed here in Deltocepha-linae: Acostemmini, new placement. A new genus and species, Ikelibeloha cristata gen. n., sp. n., are described that havean unusually modified structure of the head and a large, crested pronotum. Molecular data (28S, Histone H3 genes) wereobtained for Ikelibeloha and Iturnoria, and analyzed with other members of Deltocephalinae. Results of the phylogeneticanalyses show strong support for the monophyletic clade ((Acostemma, Eryapus), (Ikelibeloha, Iturnoria)) and thus a re-lationship between previously described Acostemmini, Ikelibeloha, and Iturnoria has strong statistical support, and aclose relationship is inferred between these and the morphologically similar Alocoelidia, Caelidioides, and Protonesis.Two new species of Alocoelidia, A. maurae sp. n. and A. chasei sp. n. are described, and the genus is redescribed. Themale genitalia of Caelidioides tristis (Signoret), Iturnoria insulana, Alocoelidia fulva, and Acostemella rubra Evans areillustrated and described for the first time. The female genitalia of A. fulva, C. tristis and I. insulana are described and thefirst and second valvulae of C. tristis are illustrated. The habitus and face of Protonesis delegorguei are illustrated and thegenus is redescribed. The characters traditionally used to define Acostemmini are reviewed with notes on their known de-grees of variation, and characters that differentiate Acostemmini from the closely related tribe Stegelytrini are discussed.The type of Malagasiella minima Evans was also examined, and Malagasiella Evans, 1954 is considered a junior syn-onym of Doratulina Melichar, 1903 (Deltocephalinae: Stenometopiini), syn. n. giving the new combination Doratulina minima (Evans) comb. n.